Mathematical topics between classical and quantum mechanics - Landsman, Nicolaas P (Springer, 2015)
Draws on two traditions: the algebraic formulation of quantum mechanics and quantum field theory, and the geometric theory of classical mechanics. These are combined in a unified treatment of the theory of Poisson algebras of observables and pure state spaces with a transition probability.